Financial Synergies and the Optimal Scope of the Firm: Implications for Mergers, Spinoffs, and Structured Finance - LELAND, HAYNE E. (Journal of Finance, 2007)
ABSTRACT Multiple activities may be separated financially, allowing each to optimize its financial structure, or combined in a firm with a single optimal financial structure. We consider activities with nonsynergistic operational cash flows, and examine the purely financial benefits of separation versus merger. The magnitude of financial synergies depends upon tax rates, default costs, relative size, and the riskiness and correlation of cash flows. Contrary to accepted wisdom, financial synergies from mergers can be negative if firms have quite different risks or default costs. The results provide a rationale for structured finance techniques such as asset securitization and project finance.